Clip Migration in Common Bile Duct: An Uncommon Complication of Laparoscopic Cholecystectomy - Pradhan, U.; Gyawali, P.; Dahal, R.; Joshi Lakhey, P. (Kathmandu University Medical Journal, 2022)
Laparoscopic cholecystectomy is the gold standard procedure for symptomatic cholelithiasis. During the procedure the cystic duct is ligated with titanium clips. Migration of these clips after cholecystectomy is a rare complication and may result in stone formation in common bile duct (CBD). We are here discussing a case of a 29 years female who presented with choledocholithiasis 10 years after laparoscopic cholecystectomy. The clip was incidentally discovered during endoscopic retrograde cholangiopancreatography (ERCP) and stone extraction. The patient was managed successfully at our center.